Figuring resurrection: Joseph as a death & resurrection figure in the Old Testament & Second Temple Judaism - Pulse, Jeffrey (Studies in Scripture and Biblical Theology, 2021)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Abbreviations -- Introduction -- Aim and Scope -- Part I: Biblical Interpretation -- Part II: The Text -- Part III: Other Texts -- Part I: Biblical Interpretation -- Chapter 1: Biblical Interpretation and the Joseph Narratives -- The Joseph Narratives -- Brevard Childs: A Canonical Approach -- Robert Alter: A Poetic Reading -- Jon Levenson -- A Narrative Reading -- R. W. L. Moberly: A Theological Interpretation -- Walter Brueggemann: A Postmodern Interpretation -- Conclusion -- Chapter 2: Reading Scripture as a Unified Theological Narrative: A Recommended Methodology -- A Recommended Methodology -- Reading Scripture as a Unified Theological Narrative -- Biblical Motifs and the Text -- A Unified Theological Narrative and the Joseph Narratives -- Part II: The Text of Genesis 37-50 -- Chapter 3: The Masoretic Text of the Joseph Narratives -- Introduction -- The Joseph Narratives -- Genesis 37 -- Genesis 38 -- Genesis 39 -- Genesis 40 -- Genesis 41 -- Genesis 42 -- Genesis 43 -- Genesis 44 -- Genesis 45 -- Genesis 46 -- Genesis 47 -- Genesis 48 -- Genesis 49 -- Genesis 50 -- Conclusion -- Chapter 4: Joseph and His Character: Perceived Problems and Difficulties -- Genesis 37: A Bad Report-Joseph the Spy -- Genesis 37: A Spoiled Son and an Arrogant Brother -- Genesis 37: Clueless -- Genesis 37: Unclean -- Genesis 38: Judah and Canaanite Women -- Genesis 38: Sexual Liaison -- Genesis 38: Who Is More Righteous? -- Genesis 39: An Ill-Advised Return -- Genesis 40: A Sudden Self-Reliance -- Genesis 41-50: Joseph the Egyptian -- Genesis 42-44: Testing, Testing, Testing -- Dysfunction and Deception: A Family Heritage -- Conclusion -- Chapter 5: The Death-and-Resurrection Motif in the Joseph Narratives -- Introduction -- The Death-and-Resurrection Motif of the Joseph Narratives.